The Bidirectional Relationship Between Obstructive Sleep Apnea and Obesity – A Literature Review - Dróżdż, Marek; Boral, Wiktoria; Czyszczoń, Alicja; Puliński, Jan; Przelaskowska, Aleksandra; Tkaczyk, Aneta; Marzec, Wiktoria; Linke, Julia; Maczkowski, Bartosz (Journal of Education, Health and Sport, 2025)
Introduction and purpose Obstructive sleep apnea (OSA) is recognized as one of the most prevalent sleep-related breathing disorders worldwide, affecting up to one billion adults aged 30 to 69 years. This disorder is characterized by recurrent episodes of upper airway collapse during sleep, leading to partial (hypopnea) or complete (apnea) cessation of airflow despite ongoing respiratory effort. These events cause intermittent oxygen desaturation and fragmented sleep architecture, resulting in significant daytime symptoms and adverse health outcomes. The current review aims to elucidate the complex bidirectional relationship between obstructive sleep apnea and obesity, emphasizing the necessity of a comprehensive and integrated clinical approach for the diagnosis, treatment, and management of these intertwined conditions. A brief description of the state of knowledge A systematic literature review was performed using PubMed and MDPI databases, encompassing original research articles, systematic reviews, and meta-analyses focusing on obstructive sleep apnea, with particular attention to publications from the last twenty years. The evidence consistently supports a reciprocal association between obesity and obstructive sleep apnea. Additionally, the effect of continuous positive airway pressure (CPAP) therapy on body weight is unclear, with weight gain primarily reported in patients who have poor adherence to the treatment. Summary Due to the lack of conclusive data, future investigations should focus on delineating the hormonal and physiological mechanisms that underpin OSA–obesity interaction, optimizing CPAP treatment protocols, and developing targeted weight management strategies tailored for this high-risk patient population. Moreover, clinicians should strongly advocate for the implementation of concurrent behavioral interventions alongside CPAP therapy to mitigate the risk of therapy-associated weight gain and improve overall patient outcomes.